Design of a Multidimensional Accounting System. - Haseman, William D.; Whinston, Andrew B. (The Accounting Review, 1976)
Abstract The article focuses on some designs of multidimensional accounting system. An accounting system is viewed as a structured database capable of supporting a class of queries or requests for data. These queries could be specific requests for data, such as the current balance of an account or the value of an inventory item, or more complicated requests, such as a profit and loss statement or a balance sheet. The traditional accounting system is oriented toward financial reports and therefore, only financial data are stored. Information on an hourly wage earner, such as number of parts produced on a given day, the average number of defects or the value added to the part, normally is not stored with the accounting data. By storing the value added information, an employee can be evaluated on terms of wage times hours versus the value added to the product. Authors' contention is that an accounting system can be viewed as an information system that supports a specific class of queries. The paper presents a process for designing a common data structure, which will support the given set of queries.